HUBUNGAN LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA MASA PANDEMIK COVID-19 (STUDI KASUS MATAHARI DEPARTMEN STORE, METROPOLITAN MALL CILEUNGSI) - Jeremia, jeremia; Elly Rasyid; Ramot P. Simanjuntak (Buletin Ekonomi, 2024)
Abstract These studies aim to examine and analyze effects of profitabilities and transfer prices on tax aggressiveness. The independent variable use are profitabilities and transfer prices. The dependent variables use is tax aggressiveness. The populations in these studies are companies in consumers good industries from 2017 to 2021 on Indonesia Stock Exchange. The secondary data collections method in which data is quantitative in form of financials report access through www.idx.co.id, the official IDX website. The sample in these studies were 25 company during observation periods of 5 consecutive year so that total samples was 125. The method of analyst of these studies use multipled linear regressions. The result of these studies indicate that profitability affects tax aggressiveness and transfer prices affect tax aggressiveness. Meanwhile, profitability and transfer price simultaneously influence tax aggressiveness. the coefficient of determination's findings indicate 13.9%. These result indicating abilities of independent variables to explained dependent variables while 86.1% is explain by another variable. Keywords: tax aggressiveness, profitability, transfer pricing